KONFLIK DALAM PEMANFAATAN DAERAH ALIRAN SUNGAI AYUNG, DI BALI ( Kajian Ekologi Manusia ) - Wardi, I Nyoman (Bumi Lestari; Vol 3 No 2, 2012)
Ayung river which is stretching along the five regencies constitutes the longes river (68.5 km) in Bali. The river has important roles in term of supplying water needed by localcommunities for subak irrigation system, for local comsumtions, tourism industries and forholding a religius ritual. The study is aimed to identify problems or conflicts which recentlyemerging to utilization of the river basin. The study was preceded by reviewing literatures,field observation, and indept-interview to the key informans. Data collected then bringanalyzed by a qualitative-description techniqueThe results of the study showed, that on line with tourism and demographicaldevelopment in Bali, there are some conflicts of interests have been emerging, including : (1)conflict between a group of farmers or regional government at upstream against middle ordownstream, (2) internal conflicts among tourism business (hotels/restourants and rafting),(3) conflicts between tourism businesses against local communities, and (4) conflicts betweenreal estates (public housing businesses) against subak institutions. In addition to those, thereare also some problems related to convertion of conserved area along the river edges.To coup with the problems/conflicts, integrated management approaches throughestablishing an institutions or forum to watch and to manage the river basin is needed. Themanagement should involve all stakeholders including local communities. All isues relatedto economical, ecological and culture aspects need to be consider in management system ofthe river basin, so that the harmony and sustainable development can be achieved.
Keywords: river basin, conflict, conserved area, sustainable development